Changes in abortion service provision in Bihar and Jharkhand states, India between 2004 and 2013. - Andreea A Creanga; Kaushalendra K Singh; Qingfeng Li; Timothee Fruhauf; Amy O Tsui (PLoS ONE)
Background The Medical Termination of Pregnancy (MTP) Act of 1971 liberalized abortion laws in India. This study examines changes in abortion service provision and characteristics of abortion providers in Bihar and Jharkhand states, India between 2004 and 2013. Methods We used state-representative data from cross-sectional surveys of reproductive health service providers we conducted in 2004 (N = 1,323) and 2012/2013 (N = 1,020). We employed chi-squared tests to examine and compare abortion providers' characteristics, and fitted separate multivariate logistic regression models for provision of surgical, medical, and any abortion services, respectively, adjusting for potential confounders to identify factors associated with abortion service provision at the two survey time points. Results Of providers interviewed in 2004 and 2012/2013, 63.7% and 84.5%, respectively, offered abortion services. Among abortion providers, 21.1% offered surgical and 10.7% offered medical abortions in 2004; 15.8% and 94.1% did so, respectively, in 2012/2013. Private providers were more likely than public providers to offer abortion services at both time points. Compared to female providers, male providers were significantly less likely to provide both surgical and medical abortions in 2004, and significantly less likely to provide surgical abortions in 2012/2013. Pharmacists and community health workers played increasingly important roles in abortion service provision, especially medical abortion, during the period. Conclusion This study documents important changes in abortion provision in the two Indian states during 2004-2013.